Online Instructions: Problems and Potentials for the Teaching of English in Indonesia - Patrisius Istiarto Djiwandono (TEFLIN Journal: A publication on the teaching and learning of English, 2000)
Abstract: This paper reports the results of a survey of a one-semester online course for students majoring in Economics, Secretarial, Computer Technology, and Language Education. The teacher created online mateÃÂrials of reading strategies along with the assignment on www.blackboard, corn, and the students were instructed to access the materials, learn them independently, and do some self-evaluated reading assignments. QuesÃÂtionnaires were then distributed to see what obstacles had hampered their efforts in learning from online materials, as well as what advantages they gained from the new instructional approach. The qualitative and quantiÃÂtative data culled from the questionnaires revealed potentials as well as some latent problems in carrying out an online teaching. The general profile that emerged was learners who were enthusiastic about learning through Internet and felt that the new approach had familiarized them with the futures technological tools, but who were mostly hampered by the lack of fund and facilities. These are discussed with special reference to the use of advanced computer technology in the teaching of English in Indonesia.